Energy policy - Mitchell, J; Allas, T; Odell, P; Appert, O (Oxford Institute for Energy Studies, 2006)
John Mitchell considers EU policies on energy supply security; Tera Allas on energy security of supply in the UK: the way forward; Peter Odell assesses public/private partnerships on the UKCS; Olivier Appert provides an overview of French energy policy.